A COMPARATIVE STUDY OF DEICTIC UNITS IN THE GERMAN TRANSLATIONS OF PARET, BUBENHEIM–ELYAS AND KHOURY - Abduraxmonova Ra’no Kosimovna (International Journal of Literature and Language Studies, 2026)
This article examines the use and translation of deictic units in the German Qur’an translations of Rudi Paret, Bubenheim–Elyas, and Adel Theodor Khoury. Deixis plays an essential role in religious discourse because it connects linguistic expressions with speaker, addressee, time, place, and textual context. The study focuses on personal, spatial, temporal, and discourse deixis and compares how these elements are rendered in the selected German translations. Special attention is given to the ways in which translators preserve, adapt, or reinterpret deictic references in order to convey the intended meaning of the original text. The analysis shows that each translator applies different strategies depending on linguistic structure, theological interpretation, and target-reader orientation.